Convective Heat Transfer and Pressure Drop over Elliptical and Flattened Tube. Issue 5 (21st December 2014) - Swain, Abhilas; Das, Mihir Kumar
Abstract : A numerical study on the effect of the effect of elliptical and flattened tube bundle geometry on the convective heat transfer and pressure drop is presented in this article. The analysis has been carried out to evaluate the performance of these bundle geometries in the design of a compact and effective single phase shell and tube heat exchanger. The temperature, velocity, and pressure drop profiles are obtained from solving the mass, momentum, and energy conservation equations. The comparison is made for inline and staggered bundle with different pitch to diameter ratio and inlet velocity for elliptical and flattened tubes. The pitch to diameter ratio is varied from 1.25 to 2.5 for Reynolds number ranging from 200 to 2000 which is in the laminar flow region. The heat transfer coefficient over the staggered and inline tube bundle decrease with an increase in pitch. The same kind of variation is also observed for the pressure drop in the case of both elliptical and flattened tube bundle. The study shows that the transverse pitch with respect to cross flow affects more than the longitudinal pitch.